Actor–network theory: A novel approach to supply chain management theory development. Issue 2 (7th February 2023) - Hald, Kim Sundtoft; Spring, Martin
Abstract: Supply chain management (SCM) researchers often conduct research using theoretical approaches and ontological assumptions adopted from other areas of management. These approaches and assumptions are valid for some aspects of SCM but may also neglect or be unsuited to other questions and concerns that are distinctive to the SCM domain. Actor–network theory (ANT) provides an alternative perspective that addresses some of the blind spots of established approaches. We begin by describing the main theoretical assumptions and the dominant ontological position of ANT, in terms of three principles: relationality, heterogeneity, and performativity. We then show how adopting these principles allows an alternative conceptualization of the supply chain and of SCM itself and discuss the methodological implications of adopting these principles for research in SCM. ANT‐inspired research can make four major contributions to the development of new SCM theory. First, ANT can provide new theoretical insights into the dynamic and fragile character of supply chains, specifically regarding how SCM systems and devices are implemented, constructed, and transformed in practice. Second, ANT can enable the development of SCM theory that leads to a better understanding of how people in SCM roles really act when managing in the supply chain space. Third, the question of what and who manages the supply chain can be explored in radically new ways. Finally, ANT can provide a complementary perspective on power in the supply chain, serving as a good lens for researchers interested in exploring the politics of representing, interpreting, and stabilizing SCM practices and systems.